If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19 = c + 11 Reorder the terms: 19 = 11 + c Solving 19 = 11 + c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1c' to each side of the equation. 19 + -1c = 11 + c + -1c Combine like terms: c + -1c = 0 19 + -1c = 11 + 0 19 + -1c = 11 Add '-19' to each side of the equation. 19 + -19 + -1c = 11 + -19 Combine like terms: 19 + -19 = 0 0 + -1c = 11 + -19 -1c = 11 + -19 Combine like terms: 11 + -19 = -8 -1c = -8 Divide each side by '-1'. c = 8 Simplifying c = 8
| 2l+2(60)=750 | | 3x+4-(6x-2)=20 | | (-16x+13)+(-20x+23)=180 | | 2(2x-12)=28 | | 21+2(60)=750 | | -2(x-3)+4=2x-1 | | -5=16+x | | -14=a-39 | | 3x^3-6x^2-189=0 | | 12x+3y-9=0 | | (6x+44)+(-10x+65)=180 | | 5x^(3/2)-25x^(1/2)+30x^(-1/2) | | 35x^6/7x^(1/4) | | 11+(-6)(3)= | | 3x+9=5x+10 | | 7x-10/4=-6 | | 0=2v-8 | | 22/2+(-6)(3) | | 5295/4.13 | | 8=-w+14 | | 7x-10/4=6 | | 3x-12x=4x+7x-16 | | 3(2z-7)=5z+17+2 | | 3x+4x-6=2 | | (22x+253)/30=11 | | (X/4)=23 | | c/2+3=-2 | | 18+x=51 | | 3y^2+15y=42 | | c/2+3-3=-2-3 | | 15y-14y+5=6 | | 5x-11=9-(4-14) |